Editorial (KEMANUSIAAN The Asian Journal of Humanities, 2011)
This issue marks the beginning of a new publication series by KEMANUSIAAN the Asian Journal of Humanities (KAJH) as it shifts from an annual to a biannual publication. This timely move happily coincides with the journal’s acceptance into the SCOPUS citation index which presents an opportune occasion for the journal to revisit the humanities discipline, to take stock of its role in knowledge advancement and its place in social development. Thus, it is fitting that this issue of KAJH carry two thought-provoking articles on the centrality of the humanities as an agent of sustainability as well as change. In the article 'Towards a Restoration of the Humanities in the Future University: Asia's Opportunity', the author argues that from the 'ruins' of Western Humanities and amidst the global changes that are taking place, there is an opportunity for the humanities to take on a leading role 'in university-based knowledge building and education'. This, the author suggests, should begin in Asian universities where there is space for reinventing the humanities befitting the 21st century glocal revolution. The second article on the humanities, 'Empowering the Humanities: A Focus on Language Studies', is a keynote address that was delivered at an international humanities conference. In keeping with the theme of the conference which is Empowering the humanities in upholding heritage, knowledge, people and nature, the paper focuses on the vital role of the humanities as an academic discipline in society and development. Drawing inspiration from the area of linguistics, a subdiscipline of the humanities, the author argues that overlaps between disciplines can and should be harnessed to empower the humanities. Crucially, the author elegantly suggests, '(c)ollaborating rather than isolating is a powerful method in the generation of new ideas for the development of society'.Indeed, it is the collaboration between disciplines in the humanities that allows for the meeting of linguistics and divine revelation in the article 'Language Acquisition, Linguistic Creativity and Achievement: Insights from the Qur'an'. The issue of language acquisition has always been the concern of the area of linguistics. In this article, however, the author draws evidence from research in the Arab context with regard to the tradition of learning the Qur’an to present an alternative view on language acquisition, creativity and attainment. The article, in essence, suggests that there is a strong relationship between learning the Qur’an by heart and language as well as scholastic achievement.The potential of the humanities to converge methods and the permeability of the area made possible the inclusion of two other articles in this issue that are diametrically opposite in terms of concern and methodology, but which fall within the scope of the humanities. The article 'A Marxist Interpretation of the Dystopian Society in the African Novel' as the title suggests is an analysis of a social concern based on literary work. Based on the writings of two 'less canonised novelists', the discussion of dystopia in fictional Africa is not only engaging, but also, provocative. Just as interesting is the issue of the effects of the global on the local in the article 'Foreign Direct Investment and Development of Electric and Electronic Products Industry in Penang State, 1970–2007'. The article discusses the impact of global changes on local socioeconomic and geographical development, particularly in the state of Penang in Malaysia, and highlights the resulting challenges that are faced by the state to remain an industrial hub.